How the New Type of Entrepreneurship Education Complements the Traditional One in Developing Entrepreneurial Competencies and Intention - Wang, Shu-Mei; Yueh, Hsiu-Ping; Wen, Pei-Chang (Frontiers in Psychology, 2019)
While business schools aim to train students with specialized professional competencies, knowledge and skills related to management and corporate functions according to their major programs, entrepreneurship education in higher education intends to develop students’ entrepreneurial competencies and intention. However, the entrepreneurial and managerial domains are not mutually exclusive but overlap to a certain extent. This study utilized National Taiwan University (NTU) as a case to explore the effects of two paths of entrepreneurial education at NTU on the development of students’ entrepreneurial competencies and intention. The aim of this study was to investigate differences in business school students’ entrepreneurial competencies and intention between those who took the Creativity and Entrepreneurship Program (CEP) and those who did not, and to explore the context limits or facilitations in entrepreneurship education of college students in different academic disciplines of management school. Results of the study showed that the CEP course did have positive impacts on all entrepreneurial competencies and intention; that the effectiveness on the attitude domains was more evident than that on the knowledge or skills domains; and that academic disciplines did have a context effect on students’ entrepreneurial competencies and intention. This study sheds further light on the “black box” of context limits or facilitations in entrepreneurship education. Implications of the study are that it may lead to a complementary framework of effectively integrating the entrepreneurial program with the business and management courses, which would better facilitate students’ learning of entrepreneurship competencies and may increase their intention to become future entrepreneurs.